Farmers Awareness on Environmental Degradation used by Modern Agricultural Technologies in a Selected Area of Meherpur District (Journal of Environmental Science and Natural Resources, 2015)
The main aim of the study was to determine the farmers awareness on environmental degradation used by modern agricultural technologies by exploring the relationships between ten selected characteristics of the farmers and their awareness. Eighty farmers of the selected village Ashrafpur under of Meherpur district constituted the sample of the study. Data were collected by interviewing the farmers using personal interview schedule during the period from August to September, 2013. Among these eighty respondents 37.5% had low, 51.25% respondents had medium and only 11.25% of the respondent had high knowledge about modern agricultural technologies. While 35% respondents had low, 55% respondents had medium and only 10 % had high knowledge about environmental degradation. Among the respondents 25% had poor, 61.25% respondents had medium and only 13.75% had high awareness about environmental degradation caused by the use of modern agricultural technologies. Out of ten independent variables, six of them, that is academic qualification, organizational participation, communication exposure, innovativeness, knowledge about the use of modern agricultural technologies and knowledge about environmental degradation had positive significant relationships with their awareness on environmental degradation caused by the use of modern agricultural technologies . Three independent variable i.e. family size, farm size, and family income had no significant relationship and only age had negative significant relationship with their awareness on environmental degradation used by modern agricultural technologies.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22186 J. Environ. Sci. & Natural Resources, 7(1): 289-294 2014